Productivity of Kale (Brassica oleracea var. acephala) and Nile tilapia (Oreochromis niloticus) culture in aquaponic systems - Afolabi, Kazir Adewale (AUC Knowledge Fountain, 2020)
Crop production and aquaculture play important roles in food security and water withdrawals and contribute to over 70% of global water consumption. The aquaponic system is a sustainable way of integrating soilless crop farming and freshwater fish farming in a single system to reduce water consumption and pollution, increase food production per unit area, thereby rendering economic benefits to the farmer. In this study, an attempt was made to assess the productivity of aquaponic systems by measuring the biomass output of fish and crop, water requirement, as well as net-financial gain of the production unit. Two aquaponic systems types were designed: integrated aqua-vegeculture (IAVC) system, and deep-water culture (DWC) system (pilot-scale evaluation). Both systems combined growing kale (Brassica oleracea var. acephala) with Nile tilapia (Oreochromis niloticus) cultured in a greenhouse setting. In each system, tilapia was stocked at 10kg/m3 while kale seedlings were planted at 25 plants/m2 density. In IAVC after 14weeks, total kale yield was 2.1kg/m2 in the first crop harvest, 4.4kg/m2 in the second crop harvest, and the total fish weight gain during the two crop harvests was 9kg. Water consumed in IAVC was 3.4% of the total water volume in the system per day. Most water quality parameters in IAVC were maintained within ranges suitable for the fish and plant. In DWC after 14 weeks, total kale yield was 5.3kg/m2 in one crop harvest and the fish weight gain was 17kg. Water consumed in DWC was 2.6% of the total water volume in the system per day. It can be concluded that aquaponic systems consume 2.6 to 3.4% of total water volume as the daily water requirement. Most water quality parameters in DWC were not suitable either for the fish or plant and there were significant symptoms of nutrient deficiency in kale. This shows that mineral supply was not efficient, thus, there was a need for nutrient supplement. Due to the presence of a mechanical and biological filters in DWC, the water quality was more efficient for fish growth than in IAVC without any filter. In contrast, the water quality parameters in IAVC were more suitable for plants growth compared to DWC. Economic feasibility was projected in the IAVC system for 3m3 fish tank volume and 10.8m2 grow bed area. The cost-benefit analysis applied an inflation rate of 14.10%, and a discount rate of 16% over 15 years. The total annual projected kale yield was 360kg and the total annual projected yield of tilapia was 120kg. Net income at the end of the first year amounted to a loss of US$2,009 with a payback period of 4 years and 5 months. This shows that an aquaponic production can generate positive net cash flow before year 5. The Internal rate of returns (IRR) was 19% and net present value (NPV) was US$4,026. The scale of production in this study is recommended as a small-scale family business.